Analysis of spherical shell structure based on SBFEM. Issue 6 (4th February 2020) - Lin, Gao; Ye, Wen-Bin; Li, Zhi-Yuan; Liu, Jun
Abstract : Purpose: The purpose of this paper is to present an accurate and efficient element for analysis of spherical shell structures. Design/methodology/approach: A scaled boundary finite element method is proposed, which offers more advantages than the finite element method and boundary element method. Only the boundary of the computational domain needs to be discretized, but no fundamental solution is required. Findings: The method applies to thin as well as thick spherical shells, irrespective of the shell geometry, boundary conditions and applied loading. The numerical solution converges to highly accurate result with raising the order of high-order elements. Originality/value: The modeling strictly follows three-dimensional theory of elasticity. Formulation of the surface finite elements using three translational degree of freedoms per node is required, which results in considerably simplifying the computation. In the thickness directions, it is solved analytically, no problem of high aspect ratio arises and transverse shear locking can be successfully avoided.